(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age. Anovulation, decreased Oocyte quality and low endometrial receptivity are the cause of infertility in women with PCOS. Anovulation is the consequence of hyperandrogenism, insulin resistance. Furthermore, the reactive oxygen species (ROS) induce oxidative stress which may be responsible for poor Oocyte quality. Melatonin is a documented powerful free radical scavenger and broad-spectrum antioxidant. Current evidence suggests that melatonin involves in ovarian physiology including follicular development, ovulation, and oocyte maturation. Present study was tried to evaluate the effects of melatonin on biochemical parameters as well as outcomes of ovulation induction by letrozole in infertile women with polycystic ovary syndrome. Method: This study including 74 women of Polycystic Ovary Syndrome (PCOS) with infertility. Intervention group received melatonin 3 mg at bed time for 8 weeks as pretreatment. Serum luteinizing hormone (LH), testosterone, anti mullerian hormone (AMH), fasting insulin, oral glucose tolerance test (OGTT) were measured at baseline and after 8 weeks. Both intervention and control group were received ovulation induction for 3 cycles by Letrozole (5 mg from cycle days 2 to 6). Intervention group continued melatonin until mature follicle achieved. The primary outcomes were biochemical changes by serum luteinizing hormone (LH), testosterone, anti mullerian hormone (AMH), fasting insulin, oral glucose tolerance test (OGTT) and ovarian responses by number of mature follicles, endometrial thickness and ovulation rate. Secondary outcome was pregnancy rate. Result: Melatonin treatment for 8 weeks significantly decreased testosterone (P <0.01) serum luteinizing hormone (<P.001), HOMA IR (P<0.01) and glucose tolerance (P<0.01). The change of anti mullerian hormone was not significant (>0.05). There was significant difference in number of mature follicles (< 0.01), mean endometrial thickness (P<0.01). The risk ratio (RR) of ovulation rate was 1.34(0.09-1.68) and pregnancy rate was 2.55 (.37-3.51). The risk ratio (RR) of pregnancy rate in relation to AMH level was 1.12(0.05-1.79) in ≤8ng/ml group and 8.65(0.25-9.59) in ≥8ng/ml group which was significant. Conclusion: After 8 weeks pretreatment and 3 cycle’s co treatment with ovulation induction by letrozole, melatonin seems to provide improved biochemical and ovarian response. Based on these results, melatonin could be considered as a potential therapeutic agent for infertile women with polycystic ovary syndrome. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 850-858